2019
DOI: 10.1186/s12874-019-0766-0
|View full text |Cite
|
Sign up to set email alerts
|

How do studies assess the preventability of readmissions? A systematic review with narrative synthesis

Abstract: Background A large number of articles examined the preventability rate of readmissions, but comparison and interpretability of these preventability rates is complicated due to the large heterogeneity of methods that were used. To compare (the implications of) the different methods used to assess the preventability of readmissions by means of medical record review. Methods A literature search was conducted in PUBMED and EMBASE using “readmission” and “avoida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 56 publications
(200 reference statements)
1
13
0
Order By: Relevance
“…In 2017, we conducted a systematic review on (the implications of) the different methods used to assess the preventability of unplanned readmissions by use of patient record review [10]. Previous studies demonstrated that health administrative databases often lack extensive information (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2017, we conducted a systematic review on (the implications of) the different methods used to assess the preventability of unplanned readmissions by use of patient record review [10]. Previous studies demonstrated that health administrative databases often lack extensive information (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…The 77 studies which were included in the previous review [10] were checked for eligibility for this review by two researchers (CB and RS) (see Additional file 2). Studies were included if they fulfilled to the following criteria: original data, primary focus on preventable readmissions, clear description of preventable readmissions and potential causes of preventable readmissions (the cause classification) (see Additional file 3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Measuring preventability, however, poses some challenges since it lacks a clear definition and objective measuring tool. This causes confusion in methodology and comparability of study results, possibly explaining the wide variety in reported preventable readmissions [5][6][7][8][9][10]. In a review on hospital admissions considered avoidable, a preventability proportion between 5% and 79% was reported [7].…”
Section: Introductionmentioning
confidence: 99%
“…This assumed that readmissions are preventable. Measuring the preventability of readmissions is a challenge, because uniform factors related to preventable readmissions and a clear definition of ‘preventability’ have not been established . Feigenbaum et al found that on average, 8.7 factors contributed to each potentially preventable readmission.…”
Section: Introductionmentioning
confidence: 99%